Strategies used by the children's education teacher for orientation and mobility of the visually impaired student - Magalhães, Alessandra Tanuri; Sankako, Andréia Naomi [UNESP]; Braccialli, Lígia Maria Presumido [UNESP] (SAGE Publications, 2014)
This study aims to identify, describe, and analyse strategies used by a teacher to support the mobility of students with visual impairment in various school environments. A female student with visual impairment in Brazil, aged 5 years, and her classroom teacher participated in the study. Their interactions were videotaped, and later, their dialogue and actions were transcribed. Six themes of analysis were elaborated, one for each support strategy used by the teacher. The results revealed that the strategies employed by the teacher often hampered the child’s orientation and mobility. This was probably the result of a lack of assistance by professionals specialised in Orientation and Mobility, as stipulated in Brazilian legislation.
Keywords: deficiência visual; orientação e mobilidade